The duration of near‐peak metamorphism from diffusion modelling of garnet zoning. (28th July 2014) - Spear, F. S.
Abstract Garnet in a staurolite–kyanite zone sample from central Vermont displays a bell‐shaped Mn growth zoning with diffusional modification over the outer 100 μm. The diffusion is driven by the prograde net transfer reaction garnet + chlorite = kyanite + biotite as is evidenced by a well‐defined resorption zone on the rim. Analysis of the reaction history and resorbed garnet composition suggests that the peak temperature attained was 620–660 °C. Diffusional modelling of the rim diffusion provides an estimate of the duration of the metamorphic episode over which significant garnet diffusion occurs. The duration is a function of the assumed peak temperature and garnet diffusivities and range from a few hundred thousand years to a few million years. Such short durations require rapid tectonic burial and exhumation of relatively thin tectonic slices.